Bifocal metastasis of melanoma to the small intestine from an unknown primary with intestinal obstruction – case report - Hedayati, Ali Akbar; Bandurski, Jędrzej; Lewandowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2013)
A 64-year-old woman was hospitalized at an internal care unit, due to growing weakness, dizziness, lack of appetite, anemia and abdominal pain. In anamnesis: past myocardial infarction, post-operative hypothyroidism, type 2 diabetes insulin-dependent, stroke, left kidney cirrhosis, gout and anemia. The physical examination did not reveal pathological changes except for skin paleness. The biochemical tests showed iron deficiency anemia and elevated Ca 125 (54.5 U/ml) (normal range: 0.00–35.00). Other markers were normal. An abdominal CT revealed a bifocal infiltration of the small intestine. Due to the increasing obstruction symptoms, the patient was operated on. A bifocal small bowel tumor was found intra-surgically. A partial resection of the jejunum and distal ileum was made. The intestines were joined end to end. The histopathological diagnosis corresponded to metastases of malignant melanoma. The postoperative course was uncomplicated. She received two cycles of dacarbazine 1000 mg/day. Due to drug intolerance, the chemotherapy was discontinued. Now, she is receiving hospice care.